From database to knowledge graph — using data in chemistry. (December 2019) - Menon, Angiras; Krdzavac, Nenad B; Kraft, Markus
Abstract : Over the last couple of decades, the scientific community has made large efforts to process and store experimental and computational chemical data and information on the world wide web. This review summarizes several databases and ontologies available on the web for researchers to use. We also discuss briefly the categories of chemistry data that are stored, its main usage and how it can be accessed and understood in the framework of the Semantic Web.